The impact of language learning experiences on language teachers’ professional practices: a case study of two language biographies - Herath, Sreemali M. (National Science Foundation: Colombo, 2020)
This study explores the impact of prior language learning experiences on second/foreign language teachers’ professional practices. Drawing on two English as a Foreign Language (EFL) teachers’ language learning biographies, this paper attempts to understand: a) the nature of nonnative speakers’ language learning experiences, b) how these experiences shape their personal practical knowledge (PPK), and c) how their PPK informs their professional practices. The findings of the study reveal that prior experiences function as a filter, shaping participants’ instructional decisions. The paper concludes with a discussion of implications for second language teacher education.
Keywords: Language learning in teacher education; Second language teacher education; Language biography; Personal practical knowledge